2023
DOI: 10.3389/fnins.2023.1161578
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture with twirling reinforcing and reducing manipulation shows a control of hypertension and regulation of blood pressure-related target brain regions in spontaneously hypertensive rat: a preliminary resting-state functional MRI study

Abstract: AimTo observe the effects of acupuncture manipulations on blood pressure and brain function in spontaneously hypertensive rats and elucidate the anti-hypertensive effect of the manipulations’ central mechanism.MethodsThis study used acupuncture twirling reinforcing, acupuncture twirling reducing, and acupuncture twirling uniform reinforcing-reducing manipulations to act on the bilateral TaiChong point of rats. The depth of acupuncture was 1.5–2 mm, and twisting was performed at a frequency of 60 times/min with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…In contemporary clinical practice, the LR3 is extensively employed to manage various conditions, including hypertension, pain, depression, hepatitis, and cognitive deficits. Several animal studies ( Lu J. et al, 2017 ; Yang et al, 2017 ; Luo et al, 2019 ; Li et al, 2023 ) have demonstrated that acupuncture at the LR3 can markedly reduce blood pressure in spontaneously hypertensive rats, with varying acupuncture techniques eliciting differential hypotensive effects. Additionally, the acupuncture at LR3 can prevent hippocampal neuronal apoptosis by augmenting the Bcl-2/Bax ratio in the hippocampal region, thereby reducing brain damage induced by hypertension ( Lu J. et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contemporary clinical practice, the LR3 is extensively employed to manage various conditions, including hypertension, pain, depression, hepatitis, and cognitive deficits. Several animal studies ( Lu J. et al, 2017 ; Yang et al, 2017 ; Luo et al, 2019 ; Li et al, 2023 ) have demonstrated that acupuncture at the LR3 can markedly reduce blood pressure in spontaneously hypertensive rats, with varying acupuncture techniques eliciting differential hypotensive effects. Additionally, the acupuncture at LR3 can prevent hippocampal neuronal apoptosis by augmenting the Bcl-2/Bax ratio in the hippocampal region, thereby reducing brain damage induced by hypertension ( Lu J. et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be associated with the activation of brain regions, including the paraventricular nucleus of the hypothalamus, arcuate nucleus, periaqueductal gray matter in the ventrolateral funiculus, and rostral ventrolateral medulla after acupuncture. [20][21][22] These activations reduce the excitability of the sympathetic nervous system and enhance vagal activity. The research has demonstrated that acupuncture at Fengchi (GB 20) can increase the expression of neuronal nitric oxide synthase in the arcuate nucleus and periaqueductal gray matter surrounding the ventrolateral aqueduct, inhibiting the activity of the sympathetic nervous system, thereby reducing blood pressure.…”
Section: Acupuncture Points Location Methods Of Insertionmentioning
confidence: 99%